2017
DOI: 10.1002/cncy.21858
|View full text |Cite
|
Sign up to set email alerts
|

Adequacy criteria for thyroid FNA evaluated by ThinPrep slides only

Abstract: In thyroid FNA examined with TP only, lowering the adequacy threshold and eliminating the requirement of 6 groups of at least 10 cells did not significantly affect test performance if cytological features associated with malignancy were absent. Cancer Cytopathol 2017;125:534-43. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 33 publications
0
14
0
1
Order By: Relevance
“…While identifying "scant but adequate" cases may be of value as part of a quality assurance program for thyroid aspiration, at the threshold used in the Bethesda system there is no difference in clinical outcome between scant and nonscant samples. Whether this is true at the lower adequacy thresholds that have been proposed is not clear [47,48,53] . Further study appears to be warranted.…”
Section: Discussionmentioning
confidence: 87%
“…While identifying "scant but adequate" cases may be of value as part of a quality assurance program for thyroid aspiration, at the threshold used in the Bethesda system there is no difference in clinical outcome between scant and nonscant samples. Whether this is true at the lower adequacy thresholds that have been proposed is not clear [47,48,53] . Further study appears to be warranted.…”
Section: Discussionmentioning
confidence: 87%
“…In such cases, a viable alternative could be the use of LBC for the repeat FNA: its diagnostic accuracy is similar to the conventional preparations and additional studies such as immunocytochemistry and molecular analysis can be easily performed . A recent paper has also shown that lowering the adequacy threshold in liquid‐based preparations does not affect test performance . In our samples, if molecular analysis was used in lieu of repeat aspiration, it would be unnecessarily used in 75% of the samples that were reclassified as benign after the second assessment.…”
Section: Discussionmentioning
confidence: 92%
“…16,17 A recent paper has also shown that lowering the adequacy threshold in liquid-based preparations does not affect test performance. 18 In our samples, if molecular analysis was used in lieu of repeat aspiration, it would be unnecessarily used in 75% of the samples that were reclassified as benign after the second assessment. In addition, repeat FNA is a cheaper alternative, which can be an important issue in developing countries or in remote centres with no direct access to modern technologies.…”
Section: Discussionmentioning
confidence: 95%
“…Quantitatively, predominantly cystic thyroid nodules have a low cellularity compared to solid thyroid nodules; qualitatively, large and predominantly cystic thyroid nodules tend to accompany intranodular changes such as cystic degeneration and/or hemorrhage, which may have poor colloid accumulation [14]. Furthermore, the amount of colloid can be diminished and appear dense, fragmented, and in droplet form during LBC preparations [20]. In our study, slides with frequent and easily identifiable colloids were classified as cytological adequacy even if they lacked the threshold of 6 groups of follicular cells; however, all of these cases exhibited low cellularity.…”
Section: Discussionmentioning
confidence: 99%